Optimization in driver’s scheduling for university shuttle bus using harmony search - Shaffiei, Zatul Alwani; Abal Abas, Zuraida; Abdul Rahman, Ahmad Fadzli Nizam; Shibghatullah, Abdul Samad; Hussin, Burairah (Publications International, 2014)
This paper is about driver scheduling which is categorized as a difficult combinatorial problem. Driver scheduling is the process of assigning shift to the drivers based on hard and soft constraints. The proposed technique is Harmony Search, which is a recently developed population-based meta heuristic optimization algorithm. This study will be implemented to UTeM Shuttle Bus. The number of drivers involved is about 25. It is viewed that the objective function evaluated by Harmony Search is less than a manual solution. Therefore, the result produced for this project is quite promising since the objective function obtained is better than the real schedule which is done manually.